2019
DOI: 10.1111/jam.14213
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity againstRalstonia solanacearumof the lipopeptides secreted from theBacillus amyloliquefaciensstrainFJAT‐2349

Abstract: Aims The aims of this study were to identify the structure of antibacterial lipopeptide (LP) produced by Bacillus amyloliquefaciens strain FJAT‐2349, to analyse the effects of the culture medium and temperature on LP production and to assess the biocontrol efficiency of the LPs against tomato bacterial wilt. Methods and Results Lipopeptides were extracted by acid precipitation and resolved in methanol and their structure was identified through LC‐QTOF‐MS/MS method. The antibacterial activities of the LPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 29 publications
(73 reference statements)
7
49
1
2
Order By: Relevance
“…Similarly, in the operational group B. amyloliquefaciens, our results demonstrated that antibacterial activity was related to iturin and fengycin, as has been reported [46,47]. Strains IMA2, IMA6, IMA8 and IMA10 were able to produce iturin or both iturin and fengycin, corresponding to a higher antibacterial activity compared with IMA1 and IMA9 without lipopeptide production and with low antibacterial activity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, in the operational group B. amyloliquefaciens, our results demonstrated that antibacterial activity was related to iturin and fengycin, as has been reported [46,47]. Strains IMA2, IMA6, IMA8 and IMA10 were able to produce iturin or both iturin and fengycin, corresponding to a higher antibacterial activity compared with IMA1 and IMA9 without lipopeptide production and with low antibacterial activity.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, there is no significant difference between the IMA2 and IMA8 in vivo assays, showing that iturin is the most important active ingredient. This is probably due to too little fengycin being secreted by IMA 8 under the same conditions, although few studies display that iturin and fengycin produced by B. amyloliquefaciens have high activity against R. solanacearum [46,47], and purified fengycin has stronger antibacterial activity than iturin [47]. By comparison, no lipopeptides are found in strains IMA 4, IMA 7 and IMA 11 except IMA4 but they also show higher disease control efficacy, possibly being associated with mechanisms of induced resistance [33,48].…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was adjusted to pH 2.0 with 3 mol/L HCl to obtain the crude lipopeptides. The extracted lipopeptides were dissolved in phosphate buffer and then lyophilized [32]. The obtained lipopeptide powder was dissolved in pure methanol for antimicrobial activity tests, for the qualitative and quantitative analyses and it was dissolved in water for the further pot experiments.…”
Section: Extraction and Identification Of The Lipopeptidesmentioning
confidence: 99%
“…Qualitative and quantitative analyses of the lipopeptides were performed using liquid chromatography quadrupole time-of-flight tandem mass spectrometry (LC-QTOF-MS/MS) technology based on previous methods [32]. The structure of the lipopeptides was estimated by their accurate mass and MS/MS fragmentation patterns according to the literatures [33][34][35][36][37].…”
Section: Extraction and Identification Of The Lipopeptidesmentioning
confidence: 99%
See 1 more Smart Citation